A Systematic Literature Review: Dietary and Cultural Shifts and Child Nutrition Status in Fishing Families - Nangi, Mohamad Guntur; Oruh, Shermina; Agustang, Andi; Lestari, Sari Arie; Yanti, Fitri (Formosa Journal of Science and Technology, 2024)
The diet and culture of fishing families are important factors in determining the nutritional status of children. However, changes in the diet and culture of fishing families have occurred over time. The review was conducted by searching for research articles published in reputable scientific journals between 2013 and 2023. The results of the review showed that shifts in the diet and culture of fishing families have negatively impacted children's nutritional status. Dietary changes from seafood to processed foods have led to decreased intake of protein and essential minerals. Cultural changes, such as changes in the identity of family cuisine, which is closely related to the family's economy, affect the family's eating environment. Dietary and cultural changes in fishing families have a major impact on children's nutritional status.